PENGARUH PEMBERIAN MULSA PLASTIK HITAM PERAK (MPHP) TERHADAP PERTUMBUHAN DAN HASIL DUA VARIETAS TANAMAN CABAI (Capsicum annuum L.) - Erni Yulia; Ahmad Riduan; Tiur Hermawati (Bioplantae, 2015)
Chili is a vegetable that has high economic value, but to increase production is hampered by high attacks of pests and diseases. One effort to improve it is by using mulch and selecting superior varieties of chili plants. The study aimed to examine the effect of Black Silver Plastic Mulch (MPHP) on the growth and yield of two chili varieties (Capsicum annuum L). The study used a Randomized Block Design (RBD) with one factor of combination of variety and type of mulch.. The combination of two varieties and mulching is as follows: P1 = (Mario variety + without MPHP), P2 = (Jatilaba variety + without MPHP), P3 = (Mario + MPHP variety), P4 = (Jatilaba + MPHP variety). To see the effect of treatment, the data were processed statistically by analysis of variance, and for further tests using the Smallest Significant Difference Test (LSD) at the level of α = 5%. The combination of the use of MPHP and two chili varieties affected plant height, number of fruit crops, yield of 2X yields, and weight vanished. The use of Mario varieties given MPHP can increase yields on variable height of chili plants, number of fruit crops, yields and weight loss. Chili Mario varieties more resistant than Jatilaba using MPHP .